Partial replacement of pork backfat with konjac gel in Northeastern Thai fermented sausage (Sai Krok E-san) to produce the healthier product - Supaluk Sorapukdee; Sujitta Jansa; Pussadee Tangwatcharin (My University, 2019)
The influence of konjac gel level on fermentation process and product qualities were assessed to evaluate the feasibility of using it as fat analog in Northeastern Thai fermented sausage (Sai Krok E-san).Five treatments of fermented sausages were formulated by replacing pork backfat with 0%, 7.5%, 22.5%, and 30% konjac gel. The changes in lactic acid bacteria (LAB) and important physicochemical properties of samples were assessed during 3 days of fermentation. After the end of fermentation at day 3, water activity (aw), instrumental texture, color, microbial counts, and sensory evaluation were compared. The best product formulation using konjac for replacing pork back fat were selected and used to compare proximate composition and energy value with control sample (30% pork backfat).An increase in konjac gel resulted in higher values of LAB, total acidity, and proteolysis index with lower pH and lipid oxidation during 3 days of product fermentation (p<0.05). It was noted that larger weight loss and product shrinkage during fermentation was observed with higher levels of konjac gel (p<0.05). The resulting sausage at day 3 with 15-30% konjac gel exhibited higher hardness, cohesiveness, gumminess, springiness, and chewiness than control (p<0.05). The external color of samples with 22.5-30% konjac gel were redder than others (p<0.05). Mold, Salmonella spp., S. aureus, and E. coli in all finished products were lower than detectable levels. Product with 15% konjac gel had the highest scores of sourness linking and overall acceptability (p<0.05).The product with 15% of konjac gel was the optimum formulation for replacing pork backfat. It had higher sensorial scores of sourness and overall acceptability than control with less negative impact on external appearance (product shrinkage) and weight loss. Moreover, it provided 46% fat reduction and 32% energy reduction than control.
Keywords: Polysaccharides Composition and Applications